Involvement of the systemic microcirculation in pediatric uveitis - Carlyn V. Kouwenberg; Julia Spierings; Evianne L. de Groot; Joke H. de Boer; Viera Kalinina Ayuso (BMC, 2023)
Abstract Background Pediatric uveitis is a severe inflammatory ocular condition that can lead to sight-threatening complications and can negatively impact quality of life. The retinal microcirculation is often affected in intermediate uveitis and panuveitis. Here, we examined the extraocular (i.e., systemic) microcirculation in pediatric uveitis cases and healthy controls using nailfold capillaroscopy (NFC). Methods We performed NFC in 119 children with noninfectious uveitis and 25 healthy pediatric controls, and assessed the following parameters: capillary density (number of capillaries/mm), dilated capillaries (apex > 20 µm), avascular area, the presence of microhemorrhages, and capillary morphology. Differences in NFC parameters between cases and controls were calculated using regression analysis after adjusting for age and sex. Results The mean (± SD) age of the patient group was 13.7 (± 3) years, with 56% females; 46%, 18%, and 36% of cases presented as anterior uveitis, intermediate uveitis, and panuveitis, respectively, with an overall mean disease duration of 4.7 (± 4.0) years. Compared to the control group, the pediatric uveitis cases had a significantly higher number of dilated capillaries/mm and a higher prevalence of ramified capillaries. Moreover, compared to the control group the intermediate uveitis cases had a significantly higher number of dilated capillaries, whereas the anterior uveitis cases had a lower capillary density and a higher prevalence of ramified capillaries. Conclusions Children with uveitis without systemic disease can present with changes in systemic microcirculation. These changes vary amongst the subtypes of uveitis.